Microbial Communities of Conducting and Respiratory Zones of Lung-Transplanted Patients - Beaume, Marie; Lazarevic, Vladimir; Köhler, Thilo; Gaïa, Nadia; Manuel, Oriol; Aubert, John-David; Baerlocher, Loïc; Farinelli, Laurent; Gasche, Paola; Schrenzel, Jacques; van Delden, Christian; , the Swiss Transplant Cohort Study; et al. (Frontiers in Microbiology, 2016)
Background: Lung transplantation (LT) is a recognized treatment for end-stage pulmonary disease. Bacteria from the recipient nasopharynx seed the new lungs leading to infections and allograft damage. Understanding the characteristics and topological variations of the microbiota may be important to apprehend the pathophysiology of allograft dysfunction. Objectives: To examine the characteristics and relationship of bacterial compositions between conducting and respiratory zones of the allograft. Methods: We performed 16S rRNA gene sequencing on bronchial aspirates (BAs) and bronchoalveolar lavages (BALs) collected in pairs in 19 patients at several time-points post-LT. Results: The respiratory zone was characterized independently of the time post-LT by a higher bacterial richness than the conducting zone (p=0.041). The phyla Firmicutes and Proteobacteria dominated both sampling zones, with an inverse correlation between these two phyla (Spearman r=–0.830). Samples of the same pair, as well as pairs from the same individual clustered together (Pseudo-F=3.8652, p<0.01). Microbiota of BA and BAL were more closely related in samples from the same patient than any sample across different patients, with variation in community structure being mainly inter-individual (p<0.01). Both number of antibiotics administered (p<0.01) and time interval post-LT (p<0.01) contributed to the variation in global microbiota structure. Longitudinal analysis of BA-BAL pairs of 2 patients showed dynamic wave like fluctuations of the microbiota. Conclusions: Our results show that post-transplant respiratory zones harbour higher bacterial richness, but overall similar bacterial profiles as compared to conductive zones. They further support an individual microbial signature following lung transplantation.